2020
DOI: 10.1007/s00592-020-01595-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to accessing insulin pump therapy by adults with type 1 diabetes mellitus: a qualitative study

Abstract: Aims Uptake of continuous subcutaneous insulin infusion (CSII) by people with diabetes (PwD) in Ireland is low and exhibits regional variation. This study explores barriers and facilitators to accessing CSII by adults with Type 1 diabetes mellitus. Research design and methods A qualitative study employing focus groups with adults with Type 1 diabetes mellitus (n = 26) and semi-structured interviews with health care professionals (HCP) and other key stakeholders (n = 21) was conducted. Reflexive thematic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 34 publications
3
28
1
Order By: Relevance
“…Similar findings are seen in international data from Canada 14 and Germany 15 . The reasons for these inequities remain largely speculative, but commencing CSII requires resources, time, staff expertise and adequate education and support for people with diabetes, 16 and deficits in any of these areas are likely to contribute.…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar findings are seen in international data from Canada 14 and Germany 15 . The reasons for these inequities remain largely speculative, but commencing CSII requires resources, time, staff expertise and adequate education and support for people with diabetes, 16 and deficits in any of these areas are likely to contribute.…”
Section: Introductionsupporting
confidence: 67%
“…There are likely multiple contributing factors to this finding. Many factors influencing uptake have been addressed in previous qualitative work, 16 with many likely applicable to losing access too. Additionally, we hypothesise that in part, the current PHARMAC public funding criteria 17 particularly in limiting access to CSII based on less healthy or deteriorating glycaemic control may be a further contributor to this increasing disparity and disadvantage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is worth acknowledging that although the use of diabetes technology is clearly associated with countries' local reimbursement strategies or health insurance plans [57], diabetes technology uptake is heterogeneous in countries that offer full reimbursements. Individual aspects such as personal attitudes or interests (ie, those of people with diabetes and, more importantly, HCPs), awareness, structure, and capacity are insurance-related determinants to improving the accessibility of diabetes technology [58]. Thus, we are aware that our proposed model may not be suitable for all pediatric diabetes clinics.…”
Section: Principal Resultsmentioning
confidence: 99%
“…15 In addition, a study evaluating insulin pump uptake in Ireland demonstrated that reimbursement alone as a cost consideration does not fully account for uptake of insulin pumps. 11 Qualitative studies are foundational in understanding the lived experience of type 1 diabetes as well as factors surrounding diabetes technology uptake and use. 10,16 These evaluations are particularly important when aiming to improve diabetes technology uptake as clinicians often misidentify or over identify barriers to diabetes technology use, which can lead to inadvertent gatekeeping and/or irrelevant solutions that are out of touch with the person's actual barriers.…”
Section: Introductionmentioning
confidence: 99%